A Chinese herbal formula "Gan-Lu-Yin" suppresses vascular smooth muscle cell migration by inhibiting matrix metalloproteinase-2/9 through the PI3K/AKT and ERK signaling pathways - Chien, Yi-Chung (BioMed Central, 2012)
BACKGROUND: This study was to explore the effects of Gan-Lu-Yin (GLY) on the migration of vascular smooth muscle cells (VSMCs) induced by fetal bovine serum and on neointima formation in a rat model of carotid artery balloon injury. METHODS: VSMCs were treated with different concentrations of GLY, and then analyzed with Flow cytometric analysis, zymography, transwell, and western blotting. SD rats received balloon-injury were analyzed with H&E staining. RESULTS: Our results showed that GLY significantly decreased the thickness of neointima. The inhibition by non-cytoxic doses of GLY of VSMCs migration was through its negative regulatory effects on phosphorylated ERK1/2, PI3K/AKT, and FAK. The data showed that GLY can inhibit the migration of VSMCs cells, and might block injury-induced neointima hyperplasia via the inhibition of VSMCs migration, without inducing apoptosis. CONCLUSIONS: These observations provide a mechanism of GLY in attenuating cell migration, thus as a potential intervention for restenosis.